Development of puzzle game learning media in social sciences subjects to improve student learning outcomes - Wulandari, Santi Agustina; Ratnawati, Nurul (Universitas Negeri Yogyakarta, 2024)
This research is aimed at (1) developing puzzle game learning media with material from the Asian Continent and Other Continents, (2) testing the feasibility of puzzle game learning media, and (3) testing the effectiveness of puzzle game learning media in improving student learning outcomes. The research uses the research and development (R&D) method with the ADDIE design. The research instrument is a questionnaire sheet and a multiple-choice question instrument. Data analysis was obtained from the pretest and posttest results, which were analyzed using the normality test, homogeneity test, and paired sample t-test. The results of this research and development are (1) the media developed is a puzzle game learning media, (2) the validity test shows that the puzzle game learning media has a